Financing private infraestructure in developing countries - Ferreira, David; Khatami, Kamran (Washington : The World Bank, 1996)
Why private infrastructure?, 1. -- Economic importance of infrastructure, 1. -- Public financing of infrastructure, 2. -- Rationale for private provision of infrastructure, 5. -- Public sector inefficiency, 5. -- Economic pricing and cost recivery, 7. -- Advances in regulation, 9. -- Need for private resources, 10. -- Potential infrastructure investment gap, 11. -- Moving toward private infrastructure, 14. -- Reforming public enterprises, 14. -- Privatization and capital market development, 17. -- Foreign investment in privatization, 18. -- Mobilizing international financing for private infrastructure, 20. -- Need for efficient contact between government and investors, 20. -- International capital and project finance flows, 22. -- Raising long-term debt, 23. -- Improving country credit worthiness, 25. -- A window for long term U.S. dollar debt, 26. -- Special investment and financing tools, 26. -- Philippines' private sector infrastructure development fund, 27. -- Colombia's private sector infrastructure financing facility, 29. -- Managing sovereing risk guarantees, 31. -- Developing local financial resources, 36. -- Implications of inadequate local financing, 36. -- The inflation challenge, 37. -- Bond markets and infrastructure finance, 38. -- Prospects in Latin America, 39. -- Emerging bond markets in east Asia, 40. -- More - advanced markets, 42. -- Role of credit rating agencies, 43. -- Developing pension funds for infrastructure finance, 45. -- Strengthening commercial banks to provide infrastructure debt, 50